Cyclodextrin-Based Nanoencapsulation of Essential Oils for Advanced Food Applications - Leontiou, Areti A.; Giannakas, Aris E. (Food Science and Engineering, 2026)
Essential Oils (EOs) are promising natural antimicrobial and antioxidant agents for food preservation. However, their direct application is hindered by high volatility, low water solubility, chemical instability, and intense sensory impact. This review evaluates Cyclodextrin (CD)-based nanostructures as a strategic solution to these limitations. By forming inclusion complexes, cyclodextrins enhance EO stability, improve aqueous dispersibility, and enable controlled release. This paper discusses the fundamental principles of cyclodextrins, explores advanced nanoformulations such as nanosponges and biopolymer composites, and reviews recent research on their application in active packaging and direct food incorporation. While challenges in scalability, regulation, and sensory acceptance remain, CD-based nanoencapsulation represents a versatile and effective approach for harnessing the full potential of essential oils in sustainable food preservation. The integration of CDs into active food packaging systems is highlighted as a particularly promising pathway to extend shelf life while aligning with consumer demand for "clean-label" products.